ZAKAT DISTRIBUTION POLICY OF UMAR BIN KHATTAB AND COVID-19 CRISIS - Azwar Iskandar; Khaerul Aqbar (Tasharruf: Journal Economics and Business of Islam, 2020)
This research aims to analyze the distribution of the zakat policy of Umar bin Khattab and to relevance it with the condition of the pandemic of COVID-19 in Indonesia. This research uses a qualitative-descriptive approach with content analysis and library research techniques. The result showed that Rasulullah SAW has confirmed to those who he made as zakat takers to distribute zakat assets taken from the rich to the poor, not returned and stored into the state treasury, which is then allowed to distribute zakat out of the area where zakat is collected due to certain factors which the priest or leader deems emergency, such as a disaster and a drought that has caused local residents to have difficulty getting supplies of much-needed staples and drinks. So it can be concluded that: (1) among the forms of Umar bin Khattab’s zakat distribution policy are: (a) distributing zakat outside the area where the zakat is collected, (b) paying great attention to illat in determining mustahik, (c) setting priorities distributing zakat and alms to the poor; (2) various policies of Umar bin Khattab have strong relevance to the current state of the COVID-19 pandemic crisis.